The role of intelligence IQ on the globalization-income inequality nexus: a threshold regression approach - Ibrahim, Saifuzzaman; A. R., Mazlina; Wan Ngah, Wan Azman Saini; Burhan, Nik Ahmad Sufian (Korea Distribution Science Association, 2021)
Globalization is an economic process responsible for the increase of interdependence of world economies. It enhances the mobility of national resources internationally via the integration of markets, trade and investments with minimal barriers to slow the flow of products and services. Although globalization has some positive impacts on the economy, it is said to be a factor in the decline of income inequality of the participating countries. However, the results of previous studies on the relationship between globalization and income inequality are inconclusive. This suggests that there are other factors influencing the relationship between the two variables. The purpose of this study is to examine the role of intelligence (IQ) in the globalization-income inequality relationship. This study employs the threshold regression technique and cross-nation observations from 117 sample nations for the period 1980–2016. The results show that the impact of globalization on income inequality in a nation relies on its IQ level. The results imply that economic globalization has a negative impact on income inequality in nations with lower IQ levels. It widens the gap between the poor and rich. While in nations with higher IQ levels, it seems to not have any significant impact on income distribution.